The Relationship between Type D Personality, Affective Symptoms and Hemoglobin Levels in Chronic Heart Failure - Kupper, Nina (Public Library of Science, 2013)
BACKGROUND: Anemia is associated with poor prognosis in heart failure (HF) patients. Contributors to the risk of anemia in HF include hemodilution, renal dysfunction and inflammation. Hemoglobin levels may also be negatively affected by alterations in stress regulatory systems. Therefore, psychological distress characterized by such alterations may adversely affect hemoglobin in HF. The association between hemoglobin and Type D personality and affective symptomatology in the context of HF is poorly understood. AIM: To examine the relationship between Type D personality and affective symptomatology with hemoglobin levels at inclusion and 12-month follow-up, controlling for relevant clinical factors. METHODS: Plasma levels of hemoglobin and creatinine were assessed in 264 HF patients at inclusion and at 12-month follow-up. Type D personality and affective symptomatology were assessed at inclusion. RESULTS: At inclusion, hemoglobin levels were similar for Type D and non-Type D HF patients (p = .23), and were moderately associated with affective symptomatology (r = –.14, p = .02). Multivariable regression showed that Type D personality (β = –.15; p = .02), was independently associated with future hemoglobin levels, while controlling for renal dysfunction, gender, NYHA class, time since diagnosis, BMI, the use of angiotensin-related medication, and levels of affective symptomatology. Change in renal function was associated with Type D personality (β = .20) and hemoglobin at 12 months (β = –.25). Sobel mediation analysis showed significant partial mediation of the Type D – hemoglobin association by renal function deterioration (p = .01). Anemia prevalence increased over time, especially in Type D patients. Female gender, poorer baseline renal function, deterioration of renal function and a longer HF history predicted the observed increase in anemia prevalence over time, while higher baseline hemoglobin was protective. CONCLUSION: Type D personality, but not affective symptomatology, was associated with reduced future hemoglobin levels, independent of clinical factors. The relation between Type D personality and future hemoglobin levels was mediated by renal function deterioration.